2018
DOI: 10.1038/s41598-018-32210-x
|View full text |Cite|
|
Sign up to set email alerts
|

The prognostic significance of heart-type fatty acid binding protein in patients with stable coronary heart disease

Abstract: To investigate the prognostic value of heart-type fatty acid binding protein (H-FABP) in patients with stable coronary heart disease (SCHD). A total of 1,071 patients with SCHD were prospectively enrolled in this Taiwan multicenter registry study, followed for 24 months. The cut-off value of H-FABP, 4.143 pg/mL, was determined using receiver operating characteristic curves. The primary cardiovascular (CV) outcome was composite CV events, defined as cardiovascular or cerebrovascular death, myocardial infarction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
(34 reference statements)
0
16
0
1
Order By: Relevance
“…Held et al found that interleukin 6, an inflammation biomarker, was independently associated with the risk of major adverse cardiac events, CV death and all-cause mortality, while hsCRP was not significantly associated with major adverse cardiac events, CV death or cancer death 8 . In our latest publication, we reported the prognostic significance of H-FABP in patients with SCHD after 24 months of follow-up 24 . The Kaplan-Meier curves of the two groups (H-FABP ≥ 4.226 ng/mL and <4.226 ng/mL) were more significantly separated from 24 months to 36 months (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Held et al found that interleukin 6, an inflammation biomarker, was independently associated with the risk of major adverse cardiac events, CV death and all-cause mortality, while hsCRP was not significantly associated with major adverse cardiac events, CV death or cancer death 8 . In our latest publication, we reported the prognostic significance of H-FABP in patients with SCHD after 24 months of follow-up 24 . The Kaplan-Meier curves of the two groups (H-FABP ≥ 4.226 ng/mL and <4.226 ng/mL) were more significantly separated from 24 months to 36 months (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Another study cited H-FABP as an independent predictor for CV outcomes in patients with stable coronary heart disease (SCHD), mainly in CV death and acute heart failure-related hospitalizations. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have investigated the role of H-FABP in patients suffering from HF with different methods over the last few years. Many studies postulate the independent relationship between H-FABP and outcome, as well as the risk of adverse CV events [40,[58][59][60][61]. In a recent study by Ho et al, for example, high levels of H-FABP were an independent risk factor for CV death and acute HF-related hospitalization in 1071 patients with chronic coronary disease [40].…”
Section: H-fabp As a Biomarker In Heart Failurementioning
confidence: 99%
“…Many studies postulate the independent relationship between H-FABP and outcome, as well as the risk of adverse CV events [40,[58][59][60][61]. In a recent study by Ho et al, for example, high levels of H-FABP were an independent risk factor for CV death and acute HF-related hospitalization in 1071 patients with chronic coronary disease [40]. In an interesting study from 2005 with 186 patients, Niizeki et al demonstrated superiority of the combined analysis of BNP and H-FABP for risk stratification in patients with CHF.…”
Section: H-fabp As a Biomarker In Heart Failurementioning
confidence: 99%
See 1 more Smart Citation